Evaluation and cytogenetic profiling of Binjharpuri cattle of India in its native tract - S.K.Dash; B.P.Sethi; P.K.Rao; B. Prakash (Journal of Livestock Biodiversity, 2025)
Physical characterization of Binjharpuri cattle was done under a project, funded by Orissa Livestock Resources Development Society (OLRDS) by collecting information on herd structure, prevailing management practices, body conformation, production and reproduction performance and socio-economic profile of the farmers rearing these cattle. Binjharpuri has recently been registered as a distinct breed of Indian cattle. Average body weight, height at withers, body length, heart girth, punch girth, tail length and horn length in males were 254.71±7.32 kg, 121.4±1.76, 126.32±2.32, 144.2±2.32, 143.2±2.31, 95.7±3.23 and 21.17±2.86 cm, respectively. The corresponding figures in females were 07.05 ±5.32 kg, 107.3±2.16, 115.1±1.14, 136.2±2.84, 146.3±3.5, 97.9±3.71 and 12.7±1.31 cm, respectively. Binjharpuri cattle had a typical Bos indicus type karyotpye.